Damage detection in precast full panel building by continuous wavelet analysis analytical method. (February 2021) - Hanteh, Mojtaba; Rezaifar, Omid
Abstract: In this research, the free vibrations of a four-story building with specific boundary conditions have been investigated and the health of the building is monitored based on experimental results using the analytical method of continuous wavelet; then, the damage that may occur to these structures has been evaluated and analyzed. The finite element software was used to model the building by the sandwich model. In this four-story building, a sandwich panel with eight layers of material (polystyrene, concrete, steel, and concrete) was used symmetrically. Then, the fourteen natural frequencies of the sandwich structure are compared with the experimental model and the shape of the main modes of the building, which is effective in monitoring the health of the structure, has been obtained. An error of less than 2.5% reveals a good match between the results of the two models. According to experimental results, the damage location was successfully identified using the coif5 function with a scale parameter of 8 compared to other wavelet functions and shows more perturbation of coefficients at the damage locations. Thus, the relative maximum and minimum jumps in the wavelet coefficients occurred at the location of the damage and by considering the maximum or minimum coefficients of the wavelet generated at the damage location as the center of damage, the damage center can be identified with an error of less than 8%. Moreover, the effects of higher modes in displaying the damage intensity are more noticeable, so that in the torsional mode of the structure, the maximum wavelet coefficients are greater and the intensity of the damage is more visible.